Nine Steps to Success - An ISO 27001:2022 Implementation Overview - Calder, Alan (IT Governance Publishing, 2024)
This is a practical guide designed to help organizations successfully implement ISO 27001:2022, the international standard for Information Security Management Systems (ISMS). The book outlines a structured, step-by-step approach to achieving compliance with the standard, covering key areas such as risk assessment, establishing security controls, and creating a culture of continuous improvement. Each of the nine steps is explained in detail, with actionable advice, best practices, and tools to ensure that organizations can implement the standard effectively, safeguard their information assets, and enhance their overall cybersecurity posture.